Compliance na administração pública: avaliação do processo inicial de implementação dos Programas de Integridade no Estado de São Paulo - Brito, Feliphe Ulisses (2024)
This project presented a study on the implementation of Compliance in Public Administration, aiming to identify whether the process adopted in the State of São Paulo to implement Integrity Programs is considering the most relevant premises related to Public Integrity and is in a position to prioritize actions based on risks and real opportunities for integrity. The study may encourage future academic research in the areas of public administration control, innovation in the management of public policies, notably regarding internal control in the public sector at the level of government entities, in the effective exercise of improving the confrontation of risks to integrity. The methodology used is characterized by its qualitative and exploratory nature, designed to deepen knowledge about the Integrity of the State of São Paulo. And, in addition, there was a comparative analysis between Integrity Programs and their methodologies and assumptions. The results demonstrated that the premises adopted by the State of São Paulo are in line with those adopted in the Union, in other states and countries, although the challenges of implementing and monitoring the programs in progress must be observed very carefully to correct any deviation that may occur. may occur